The Contribution of English Language Mastery toward Sustainable Tourism in Gorontalo - Dahlia Husain; Ana Mariana; Yulan M. Puluhulawa; Desrika Talib; Happy Anastasia (Journal of Universal Community Empowerment Provision, 2021)
The main objective of this community service activity is to increase the knowledge and understanding of the Dumati village community in general about the importance of English language in relation to managing tourist objects. The future of the world tourism industry has such a bright prospect as stated by the World Tourism Organization (WTO), even the world tourism organization estimates that tourism will grow with an average growth of 4.2% per year. One of the regions that will experience the greatest growth rates are countries in Asia, including Indonesia. Of course, it is very important for the parties to receive foreign language assistance to the community in implementing the concept of tourism for the realization of sustainable tourism. And how to do it so that tourists do not experience language barriers so that sustainable tourism can be realized. The current community service uses focus group discussion and in-depth interviews that aims to develop the community’s awareness toward the importance of English language mastery as the key factor for sustainable tourism in Gorontalo. This activity received a very good response and went well. Dumati village officials and the village community were very enthusiastic about participating in this seminar, it was seen from the many people who participated by asking questions and discussing the concept of English language ​​that could be developed in the Embung Dumati tourism village. This community service is hoped to form basic information on how’s the community’s level of English and how to develop from there.